Estimation of Some Genetic Parameters in Faba Beans (Vicia faba L.) Affected by Nitrous Acid Mutagen - Jawad AL-Shamma, Laith Mohammed (Iraqi Journal of Science, 2023)
To estimate some of the genetic parameters and genotypic phenotypic coefficient of variation and to find the interaction between varieties and generations in the morphological traits and yield,yield components. Three varieties of Faba beans were treated by nitroso acid mutagen, field experiments were conducted during 2010-2013. The results showed that variances values were different among traits, and the values of genetic and phenotypic variance were greater than the environmental variance values for most of the traits. Heritability in the broad sense has reached the highest value in most of the studied traits for M1 and M2 generations. Heritability in the broad sense varied among the traits. Highest heritability in most of the traits in the M1 generation because of the high values of genetic variation and lower values in the protein percentage and yield protein. Also, in the M2 generation was the highest heritability in most of the studied traits due to the high genetic variation and low environmental variance ratio and less values in the traits, number of seeds/pod and protein percentage were 59.39 and 18.39, respectively. It also shows that the values of the coefficient of phenotypic variance and coefficient of genetic was convergent slightly for all the traits of the M1 generation and the M2. This leads to increase the coefficient of phenotypic variance over genetic in number of pods/plant and number of seeds/pod of two generations, protein percentage and protein yield in the M1 generation. it was shown that the coefficient of genotypic varaince and the coefficient of phenotypic varaince in M1 generation was low values in most studied traits except in number of branches per plant , yield seed and protein yield , wheares protein percentage reduced in coeffecient of phenotypic variance and coefficient of genotypic varaince in M2 generation. Zaina variety was superior in the M1 generation traits such as flowering early, plant height, leaf area index, number of branches/plant, number pods/plant, seed weight, seed yield and protein yield. It can be conclude that M1 generation was that best in heritability in the broad sense, coefficient of genetic variance and coefficient of phenotypic variance in most studied traits.